Determinant of success factors in intelligent transport system (ITS) implementation in Jakarta - Khansa Nadhifa; Zulkarnain (Communications in Humanities and Social Sciences, 2021)
As the capital city of Indonesia, Jakarta has always become the cornerstone of economic development in this country. This condition then creates a logical consequence in which one of the crucial problems is transportation management implicating the congestion levels. This research is an initial attempt to design a structural framework of conceptual relationships among the determinants of the implementation of the intelligent transport system (ITS) in the land transportation system in Jakarta. The eight factors that affect the development of ITS strategy include funding, skills, operational guidance, human resources, utilization of available data, political policies, cooperation between parties, and socio-economic benefits. The Fuzzy-Total Interpretive Structural Modeling (TISM) method was applied to develop a structural framework that can provide greater flexibility to express the level of influence using fuzzy numbers. On the other hand, the Matrice d'Impacts CroisÃ©s Multiplication AppliquÃ©e un Classement (MICMAC) analysis method was used to improve the understanding and classification of factors based on the driving forces and interdependencies between factors. We found out that the skill was a driving factor that had the highest level of driving force compared to other factors and the success of ITS services in Jakarta can be judged from the socio-economic benefits because this factor was found to be determined by the sustainability of other factors.